Differential expression of inflammation-related genes in IL-4 transgenic mice before and after the onset of atopic dermatitis skin lesions. Issue 1 (February 2016) - Bao, Lei; Zhang, Huayi; Mohan, Girish C.; Shen, Kui; Chan, Lawrence S.
Abstract: IL-4 plays an important role in the pathogenesis of atopic dermatitis (AD), a common chronic inflammatory skin disease. We have generated IL-4 transgenic (Tg) mice by over-expressing IL-4 in the epidermis. These mice spontaneously develop chronic pruritic inflammatory skin lesions, which meet the clinical and histological diagnostic criteria for human AD. Systemic survey of immune-related genes in this mouse model, however, has not been performed. In this study, we utilize PCR array technique to examine hundreds of inflammation-related genes in the IL-4 Tg mice before and after the onset of skin lesions as well as in their wild type (WT) littermates. Only those genes with at least 2-fold up-regulation or down-regulation and with a P-value of less than 0.05 in comparison to WT controls were identified and analyzed. In the skin lesions, many chemokines, pro-inflammatory cytokines, and other AD-related factors are dysregulated compared to the wild type mice. Particularly, CXCL5, IL-1β, IL-24, IL-6, oncostatin M, PTGS2, FPR1 and REG3γ are up-regulated several hundred-fold. In the pre-lesional group that shows no obvious skin abnormality on clinical observation, 30 dysregulated genes are nevertheless identified though the fold changes are much less than that of the lesional group, including CCL6, CCL8, CCL11, CCL17, CXCL13, CXCL14, CXCR3 and IL-12Rβ2. Finally using ELISA, we demonstrate that 4 most dramatically up-regulated factors in the skin are also elevated in the peripheral blood of the IL-4 Tg mice. Taken together, our data have identified hundreds of dysregulated factors in the IL-4 Tg mice before and after the onset of skin lesions. Future detailed examination of these factors will shed light on our understanding of the development and progression of AD and help to discover important biomarkers for clinical AD diagnosis and treatment. Highlights: IL-4 is essential for the pathogenesis of atopic dermatitis (AD). We performed PCR array analysis to study differential gene expression in IL-4 transgenic mice. We identified numerous dysregulated genes in this AD mouse model. We used ELISA to detect elevated serum levels of several AD-relevant factors.